2009
DOI: 10.17925/eor.2009.02.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Levofloxacin Eye Drops – A Microbiological Perspective

Abstract: Levofloxacin is a later-generation antibacterial agent of the fluoroquinolone class that exhibits a broad spectrum of in vitro activity. It has been demonstrated to be effective in the treatment of a wide range of community-and hospital-associated infections. 1 This review presents a microbiological perspective of the use of levofloxacin for topical treatment of bacterial external ocular infections, presenting in vitro, pharmacokinetic and clinical trials data. Levofloxacin eye drops were launched in several E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Other protocols were also used, such as exposure to the 5% PVI technique for 2 minutes before IVI in France. [19][20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…Other protocols were also used, such as exposure to the 5% PVI technique for 2 minutes before IVI in France. [19][20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…However, LVF demonstrated higher antibacterial potency towards Gram-negative micro-organisms. Due to its higher corneal penetration and low development of resistance compared to other molecules of the same class [ 1 ], LVF displays higher activity than moxifloxacin against H. influenzae and P. aeruginosa [ 12 ]. Furthermore, Wang et al [ 13 ] demonstrated in a retrospective study covering the period 2010–2013 that, among eight assayed antibiotics belonging to four categories (cephalosporins, quinolones, aminoglycosides, and phenicols), LVF showed to be more active than neomycin (aminoglycosides class) towards strains responsible for internal ocular infections, but not for external infections.…”
Section: Introductionmentioning
confidence: 99%